2023
DOI: 10.3389/fpsyg.2023.1101535
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of epilepsy on the linguistic-cognitive profile of children with ASD: A systematic review of the literature

Abstract: IntroductionThe prevalence of comorbidity between epilepsy and Autism Spectrum Disorder (ASD) in the pediatric age increased significantly in recent years. The onset of epilepsy negatively influences the abilities of the user with ASD. Thus, epilepsy will be a disabling factor that will reduce the cognitive-linguistic skills of users with ASD. The main objective of this work is to review the current scientific literature and to compare the relationship of epilepsy on the development of cognitive and linguistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 61 publications
0
7
0
4
Order By: Relevance
“…La población infantil con esta comorbilidad experimentará un retroceso significativo en la adquisición del lenguaje, pudiendo no adquirir lenguaje expresivo hasta los 5 o 6 años. Además de ello, los estudios actuales indican que en el 52% de las personas con TEA y epilepsia, se experimenta una regresión en sus hitos de desarrollo madurativo (Cano-Villagrasa et al, 2023). De la misma manera, los procesos cognitivos y de funcionamiento ejecutivo se ven afectados por las limitaciones en el lenguaje (Rossi et al, 2013).…”
Section: Características De Las Alteraciones Lingüísticas Y Otras Fun...unclassified
See 2 more Smart Citations
“…La población infantil con esta comorbilidad experimentará un retroceso significativo en la adquisición del lenguaje, pudiendo no adquirir lenguaje expresivo hasta los 5 o 6 años. Además de ello, los estudios actuales indican que en el 52% de las personas con TEA y epilepsia, se experimenta una regresión en sus hitos de desarrollo madurativo (Cano-Villagrasa et al, 2023). De la misma manera, los procesos cognitivos y de funcionamiento ejecutivo se ven afectados por las limitaciones en el lenguaje (Rossi et al, 2013).…”
Section: Características De Las Alteraciones Lingüísticas Y Otras Fun...unclassified
“…Asimismo, los resultados del estudio de (Cano-Villagrasa et al, 2023) permiten afirmar que la pragmática del lenguaje estará más limitada que en las personas que solo dispongan de un diagnóstico de TEA o epilepsia como diagnóstico principal. Todo ello es debido a que esta función se describe en estos perfiles con alteraciones en la interacción social, desconexión del entorno que le rodea, así como dificultades en los aspectos básicos de comunicación social como el contacto ocular, la intención comunicativa o el mantenimiento de la conversación con otro interlocutor.…”
Section: Nota: Adaptado De Cano-villagrasa Et Al (2023)unclassified
See 1 more Smart Citation
“…However, the situation is worsened if both disorders are present in the same person. Thus, if a person with ASD also has comorbid epilepsy, this will lead to an increase in the frequency and severity of autism symptoms, causing greater difficulties in areas such as communication, social interaction, learning, behavior, and emotional regulation (Gutiérrez-Ruiz, 2019;Cano-Villagrasa et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing awareness of the importance of recognizing emotional and behavioral conditions as part of assessment and diagnosis (Begeer et al, 2008). However, reported rates of behavioral or emotional problems vary considerably from one study to another (Cano-Villagrasa et al, 2023). For instance, rates of anxiety reported by parents in children with ASD and epilepsy range from 22 to 84% (Gadow et al, 2005;Pearson et al, 2006;Simonoff et al, 2008;Kanne et al, 2009;White and Roberson-Nay, 2009;Mattila et al, 2010;MacNeil and Mostofsky, 2012), and stress problems have been identified in 31 to 80% of this population (Couturier et al, 2005;Oyane and Bjorvatn, 2005;Allik et al, 2006;Dominick et al, 2007;Krakowiak et al, 2008;Souders et al, 2009).…”
Section: Introductionmentioning
confidence: 99%